The social conditions of possibility of “flop”: production, intermediation and reception - Isabelle Mayaud; Alexandre Robert (Transposition)
For the tenth issue of the journal Transposition. Musique et sciences sociales on the theme of “flops” and coordinated by Sarah Benhaïm and Lambert Dousson, we wished to discuss this topic with three young researchers in social sciences whose doctoral research focused on the different levels of circulation of musical goods – production, intermediation, reception – and how they interrelate. We decided to interview them together, in order to obtain a variety of perspectives on the complex object that is the musical “flop” and to have the benefit of seeing these different views side by side.The following exchanges are the result of an interview conducted on Friday, January 29, 2021 via a shared online document. The interviewees were invited to connect to it simultaneously for a period of several hours in order to answer questions that had been previously entered by the interviewers. Beyond its obvious convenience in times of pandemic and restricted access to public meeting places, this experimental interview process was chosen and tested for the possibilities it seemed to offer in terms of discursive production and scientific exchange. Halfway between a live, oral group interview via videoconference (where the responses are recorded and then transcribed) and a collective interview carried out entirely via email (where the different responses are written and then compiled offline), the aim here was to encourage a form of spontaneity and interactivity between the participants while allowing a certain degree of self-reflection and formalization of the answers. Being connected to a shared document, where it was possible to read everything that was written in real time, encouraged each participant to react or adjust to the others’ comments, leaving the freedom to clarify, amend or correct their own answers over the relatively long duration of this virtual meeting. The resulting text was then proofread and edited by the two interviewers before being validated by the three interviewees. The footnotes were written by the interviewees.